BEDTools: The Swiss‐Army Tool for Genome Feature Analysis. Issue 1 (8th September 2014) - Quinlan, Aaron R.
Abstract: Technological advances have enabled the use of DNA sequencing as a flexible tool to characterize genetic variation and to measure the activity of diverse cellular phenomena such as gene isoform expression and transcription factor binding. Extracting biological insight from the experiments enabled by these advances demands the analysis of large, multi‐dimensional datasets. This unit describes the use of the BEDTools toolkit for the exploration of high‐throughput genomics datasets. Several protocols are presented for common genomic analyses, demonstrating how simple BEDTools operations may be combined to create bespoke pipelines addressing complex questions. Curr. Protoc. Bioinform . 47:11.12.1‐11.12.34. © 2014 by John Wiley & Sons, Inc.